Road to Knowledge - Černevičiūtė, Sigita (Lietuvos istorijos studijos, 2017)
About the thesis of Gražina Sviderskytė “Steponas Darius’ and Stasys Girėnas’ file: The historical process, approach, and the evolution of narrative”